2024
DOI: 10.1088/2040-8986/ad49b1
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in P3HT:PCBM solar cells through experimental and simulated techniques

Taoufik Chargui,
Fatima Lmai,
Abdellah Erraji

Abstract: Organic solar cells are a promising alternative in photovoltaics due to their low manufacturing cost and flexibility. In this study, we developed an organic solar cell of structure (ITO/PEDOT:PSS/P3HT:PCBM/Al) where the active layer is represented by P3HT:PCBM. Experimental studies revealed that this layer has an energy gap of 1.9 eV and a good absorption coefficient of 〖3×10〗^5 〖cm〗^(-1). Using analytical and experimental methods based on (J-V-T) curves, we extracted the key parameters of our device, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…SCAPS 1D works on the basis of three fundamental equations: the Poisson equation and the continuity equations for electrons and holes. These equations are defined as equations ( 1)-(3) [4,17,37,38].…”
Section: Simulation Methodology and Materials Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…SCAPS 1D works on the basis of three fundamental equations: the Poisson equation and the continuity equations for electrons and holes. These equations are defined as equations ( 1)-(3) [4,17,37,38].…”
Section: Simulation Methodology and Materials Propertiesmentioning
confidence: 99%
“…In each study, the aim is to determine the optimum parameters that can be used to achieve maximum efficiency. The greater the thickness of the absorber layer, the more solar photons it can absorb [5,38]. However, it has been shown that charge carrier recombination can occur when the thickness exceeds a certain limit, which is due to the lengthening of the escape path for charge carriers outside the depletion region [17].…”
Section: Effect Of the Thickness And Carrier Density Of The Absorbent...mentioning
confidence: 99%
See 2 more Smart Citations